Current Perspectives Regarding Stem Cell-Based Therapy for Liver Cirrhosis - Kyeong-Ah Kwak; Hyun-Jae Cho; Jin-Young Yang; Young-Seok Park (Canadian Journal of Gastroenterology and Hepatology)
Liver cirrhosis is a major cause of mortality and a common end of various progressive liver diseases. Since the effective treatment is currently limited to liver transplantation, stem cell-based therapy as an alternative has attracted interest due to promising results from preclinical and clinical studies. However, there is still much to be understood regarding the precise mechanisms of action. A number of stem cells from different origins have been employed for hepatic regeneration with different degrees of success. The present review presents a synopsis of stem cell research for the treatment of patients with liver cirrhosis according to the stem cell type. Clinical trials to date are summarized briefly. Finally, issues to be resolved and future perspectives are discussed with regard to clinical applications.